Pengambangan Kota Sukabumi Dalam Mewujudkan 'Sukabumi Cyber-City' - Syarif Budhirianto (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2017)
Sukabumi Cyber City (SSC) is the flagship program of Sukabumi City Government in the field of information and communication technology (ICT) in providing faster and cheaper public services. The focus of the study is to describe the development of the SSC program as a medium for communication and information, as well as to explain the policy of development of government apparatus resources in support of the program. The research is qualitative descriptive, by conducting in-depth interviews with key informants within the Office of Communication and Informatics (Diskominfo) of Sukabumi City. The result of the research shows that the development of cyber-city concept has been done in synergy with all existing working units of the regional apparatus, that is by bringing together the common commitment and responsibility in facing the development strategy of ICT area continuously. Transparent information policy through this program is technically still lacking, because the process of screening news content must be through the stakeholders (stakeholders). Development of education and training system in forming government apparatus resource is done by knowledge sharing which is based on learning by doing directly practiced every training material, while the quality of apparatus resource needs to be improved both from managerial aspect and technical capability in ICT field, and also support and the government's commitment to the concept of cyber-city that is aligned with the Jabar Cyber Province program.Keywords: Development, Sukabumi, cyber-city ABSTRAKSukabumi Cyber-city (SSC) merupakan program unggulan Pemerintah Kota Sukabumi di bidang teknologi informasi dan komunikasi (TIK) dalam memberikan pelayanan publik yang lebih cepat dan murah. Fokus kajian adalah mendeskripsikan pengembangan program SSC sebagai media komunikasi dan informasi, serta memaparkan kebijakan pengembangan sumber daya aparatur pemerintah dalam mendukung program tersebut. Penelitian bersifat deskriptif kualitatif, dengan melakukan wawancara mendalam dengan informan kunci di lingkungan Dinas Komunikasi dan Informatika (Diskominfo) Kota Sukabumi. Hasil penelitian menunjukkan pengembangan konsep cyber-city telah dilakukan secara sinerjis dengan seluruh Satuan Kerja Perangkat Daerah yang ada, yakni dengan menyatukan kesamaan komitmen dan tanggungjawab dalam menghadapi strategi pembangunan daerah TIK secara berkelanjutan. Kebijakan transparan informasi melalui program ini secara teknis masih kurang, karena proses screening konten berita harus melalui para pemangku kepentingan (stakeholders). Pengembangan Sistem pendidikan dan pelatihan dalam membentuk sumber daya aparatur pemerintah dilakukan dengan knowledge sharing yang berbasis pada learning by doing yang langsung dipraktekan setiap materi pelatihan, sedangkan kualitas sumber daya aparat perlu ditingkatkan , baik dari aspek manajerial maupun kemampuan teknis di bidang TIK, serta dukungan dan komitemen pemerintah terhadap konsep cyber-city yang diselaraskan dengan program Jabar Cyber Province.Kata kunci: pengembangan, Sukabumi, cyber-city